Anchoring of tungsten on g-C3N4 layers towards efficient photocatalytic degradation of sulfadiazine via peroxymonosulfate activation - Tan, Filiz Buyuker; Karadirek, Seyda; Tuna, Ozlem; Şimsek, Esra Bilgin (Elsevier Science Sa, 2025)
In this study, the catalytic efficiency of graphitic carbon nitride (g-C3N4) was improved by doping tungstate (W). By performing a facile calcination method, the W atoms were placed in the -N and -O-included bonds in the triazine units of g-C3N4, resulting in the generation of new oxygen vacancies, narrowed band gap structure, enhanced light absorption ability and limited recombination of photoactive species as well as the formation of new radicals via W-redox cycles driven by peroxymonosulfate (PMS) activation. In visible light(Vis)/PMS process, the integration of W into the graphitic carbon nitride (W-CN@3) remarkable increased the catalytic activity for sulfadiazine (SDZ) degradation: from 27.9 % to 81.2 %. The W-CN@3 sample showed efficient performance at neutral pH and its performance was enhanced by increasing catalyst dosage and PMS concentration. Chemical scavenging experiment illustrated that the W-CN@3/Vis/PMS-driven removal system was mainly driven by super oxide and sulfate radicals, also hydroxyl and photoinduced holes contributed to the decomposition process. This work provides the understanding the potential and applicability of W-doped graphitic carbon nitride materials in PMS activated-antibiotic degradation under visible light irradiation.
Keywords: Peroxymonosulfate; Single atom tungstate; Graphitic carbon nitride; Sulfadiazine